REDUPLIKASI BAHASA DAYAK NGAJU DALAM CERITA-CERITA TAMBUN DAN BUNGAI SERTA IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Andelia Tritia; Petrus Poerwadi; Paul Diman; Noor Hidayat; Mariani Mariani (Universitas Palangka Raya, 2022)
Reduplication is a study of morphology regarding the process of repeating words, either in whole or in part, with varying phonemes or not, in combination with affixes or not, and becomes a language unit as a phonological and grammatical tool. This research was conducted to find out how the form and meaning of the reduplication of the Ngaju Dayak language in the stories of Tambun and Bungai are found in the book